Factor Affecting Local Resident’s Perception for Tourism Development in Agropolitan Area Pacitan Regency - Rizha Hardyansah; Luchman Hakim; Rita Parmawati (Postgraduate School Universitas Brawijaya, 2021)
Tourism is a potential services sector, integrating it with the Agropolitan concept to support rural area development is necessary. However, in its development the role of public perception must still be taken into account. The research aim of this research were to determine the role of factors (natural resources, human resources, social resources, and infrastructure) on community perceptions related to tourism development in the Pacitan Regency Agropolitan Area. Respondets from this research were 200 respondents based on the Slovin formula, and each respondent was given a questionnaire consisted of five components such as Natural Resources (X1), Human Resources (X2), Infrastructure Facilities (X3), Social Resources (X4), and Perceptions related to Tourism Development in Pacitan Agropolitan Area (Y). Data Analysis was conducted using multiple regression analysis with SPSS 16.0. The result show that natural resources, human resources, target facilities, and social resources influence the dependent variable, namely Community Perception related to tourism development in the Pacitan Agropolitan Area by 35.6 %. While the remaining 64.4% is influenced by other variables not included in this study. In addition, all of these variables have a significant influence on the variable perception of the main community on the variable human resources, social resources, and infrastructure.Keywords: Agropolitan, Perception, Tourism Development